Policing Dissent : Social Control and the Anti-Globalization Movement - Fernandez, Luis A., 1969- (Book collections on Project MUSE., 2008)
In November 1999, fifty-thousand anti-globalization activists converged on Seattle to shut down the World Trade Organization?s Ministerial Meeting. Using innovative and network-based strategies, the protesters left police flummoxed, desperately searching for ways to control the emerging anti-corporate globalization movement. Faced with these network-based tactics, law enforcement agencies transformed their policing and social control mechanisms to manage this new threat. Policing Dissent provides a firsthand account of the changing nature of control efforts employed by law enforcement agencies.